2010
DOI: 10.4314/jfecs.v35i1.52924
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotics: An update

Abstract: Prebiotics: an update OpsommingEen van die opwindendste tendense in die hedendaagse voedselbedryf is die soeke na funksionele voedsels, oftewel voedsels wat gesondheid bevorder en/of die risiko vir chroniese siektes verlaag, bo en behalwe die voedingswaarde daarvan. In hierdie opsig speel probiotika en prebiotika 'n belangrike rol. Probiotika (voedsels wat lewendige mikrobes bevat) is alombekend en word geassosieer met 'n hele aantal gesondheidsvoordele. Prebiotika (selektief gefermenteerde voedselbestanddele … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
(83 reference statements)
0
15
0
Order By: Relevance
“…It has been reported that the consumption of prebiotics could double the pool of SCFA in the alimentary tract. These SCFA acidify the gastrointestinal environment, which is beneficial for the development of probiotic bacteria and disadvantageous to the growth of pathogens (Blaut ; Venter ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the consumption of prebiotics could double the pool of SCFA in the alimentary tract. These SCFA acidify the gastrointestinal environment, which is beneficial for the development of probiotic bacteria and disadvantageous to the growth of pathogens (Blaut ; Venter ).…”
Section: Discussionmentioning
confidence: 99%
“…Among fructans, inulins are the simplest and most widely studied. They are naturally present in various plant species such as chicory, onion, garlic, asparagus, leek, and so on (Venter ).…”
Section: Increasing Enhancers Of Iron and Zinc Absorptionmentioning
confidence: 99%
“…Bifidogenic oligosaccharides increase the level of nutrient supplementation and enhance nutrient solubility (Farmer, 2002). Some of these effects include better mineral absorption, alleviation of constipation and irritable bowel syndrome, protection against colon cancer, enhancement of the immune system, anticarcinogenic effects and lowering of cholesterol (Davis & Milner, 2009;Manning & Gibson, 2004;Tuohy et al, 2003;Venter, 2007). Supplementation of diet with oligofructose and inulin-type oligosaccharides significantly lowers serum triglycerols and phospholipids.…”
Section: Beneficial Effects Of Prebioticsmentioning
confidence: 99%